Green Algae (Chlorophyta, Charophyta) of the Water Bodies of Slobozhanskyi National Nature Park (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: What is the species diversity and taxonomic structure of green algae in the water bodies of Slobozhanskyi National Nature Park (Ukraine)? Locations: "Slobozhanskyi" National Nature Park, Kharkiv region, Ukraine Methods: Field collection, laboratory identification, floristic and ecological analysis Nomenclature: Tsarenko et al. 2024, www.algaebase.org Results: The algal flora of the Slobozhansky National Nature Park comprises 176 species of chlorophyte and charophyte algae, classified into 2 divisions, 6 classes, 16 orders, 32 families, and 71 genera. Among these, charophyte algae are the most numerous, a distribution attributed to the typology of the park's water bodies, particularly the dominance of swamps as the primary waterbody type. A taxonomic analysis confirmed the prevalence of Charophyta, which account for 100 species (56.8 %) and hold leading positions across all taxonomic levels. Chlorophyta comprised 76 species, accounting for 43.2% of the total. The species distribution across water bodies was uneven, ranging from 1 to 78 species. This variability is primarily influenced by the morphometric features and water levels of the respective bodies. Charophyte algae were predominant in most bodies, as evidenced by their higher occurrence coefficient values. Ecological analyses provided further insights into the habitat preferences of the algae. Water acidity assessments revealed a predominance of indifferent species and acidophiles. Salinity analyses indicated a dominance of indifferent species. Saprobity indices, with most species classified as oligosaprobic and beta-mesosaprobic, placed the water quality of the park's bodies within classes II–III, corresponding to clean and moderately clean waters. Notably, the study identified several rare species for Ukraine's algal flora, seven new records for the Kharkiv region, and two species listed in the Red Data Book of Ukraine: Bambusina borrei and Roya anglica.
Keywords: biodiversity, Left-Bank Forest Steppe, Kharkiv region, charophyte and chlorophyte algae, rare species, ecological groups of algae